The Sacred Landscape of Dra Abu el-Naga during the New Kingdom : People Making Landscape Making People - Jiménez-Higueras, María de los Ángeles, (Culture and History of the Ancient Near East ;, 2020)
In The Sacred Landscape of Dra Abu el-Naga during the New Kingdom, Ángeles Jiménez-Higueras offers the reconstruction of the physical, religious and cultural landscape of Dra Abu el-Naga south and its conceptual development from the 18th to the 20th Dynasties (1550-1069 BC). A wider insight into the Theban necropolis is provided, including the position played by the Dra Abu el-Naga cemetery within the Theban funerary context understood as an inseparable complex of diverse components. For this study, Ángeles Jiménez-Higueras has reconciled textual and archaeological perspectives with theories relating to Landscape Archaeology, which efficiently manages to compile and to link prosopographical-genealogical, archaeological and GIS (Geographical Information System) data.